2004
DOI: 10.1016/j.visres.2004.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Center-surround antagonism in spatial vision: Retinal or cortical locus?

Abstract: Mach and Hering had early advanced a model of spatial visual processing featuring an antagonistic interaction between adjoining areas in the visual field. Spatial opponency was one of the first findings when single-unit studies of the retina were begun. Not long afterwards psychophysical experiments revealed a center-surround organization closely matching that found in the mammalian retina. It hinged on the demonstration of reduction of sensitivity in a small patch of the visual field when its surround was cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Finally, the backward masking strength is non-monotonically related to mask size ( Figure 5, solid lines), whereas increasing the inner diameter of the surround mask leads to a steep, monotonic decrease in masking ( Figure 5, dashed lines). Similar dependency on mask size has previously been reported in brightness processing (Crawford, 1940;Westheimer, 1967Westheimer, , 2004 and in simultaneous contrast masking (Yu & Levi, 1997). Petrov and McKee (2006), also studying simultaneous contrast masking, found an exponential decline in surround suppression with increas-ing target-surround distance.…”
Section: Discussionsupporting
confidence: 82%
“…Finally, the backward masking strength is non-monotonically related to mask size ( Figure 5, solid lines), whereas increasing the inner diameter of the surround mask leads to a steep, monotonic decrease in masking ( Figure 5, dashed lines). Similar dependency on mask size has previously been reported in brightness processing (Crawford, 1940;Westheimer, 1967Westheimer, , 2004 and in simultaneous contrast masking (Yu & Levi, 1997). Petrov and McKee (2006), also studying simultaneous contrast masking, found an exponential decline in surround suppression with increas-ing target-surround distance.…”
Section: Discussionsupporting
confidence: 82%
“…Kunken, Sun, and Lee (2005) confirmed Oehler's basic result but concluded from differences in the surround part of Westheimer's curve that both retinal and cortical mechanisms contributed to that curve. In summary, Westheimer's paradigm is rather useful for estimating receptive field sizes psychophysically (Westheimer, 2004).…”
Section: Spatial Summationmentioning
confidence: 99%
“…Furthermore, changes in neuronal size have been shown in the lateral geniculate nucleus, and functional imaging studies have suggested that the lateral geniculate nucleus is dysfunctional (Anderson & Swettenham 2006;Wiesel & Hubel 1963a;von Noorden & Crawford 1992;von Noorden et al 1983). Retinal abnormalities also have been found (Arden et al 1980;Westheimer 2004;Williams & Papakostopoulos 1995). Retinal involvement remains controversial since electrophysiological research and studies evaluating optical imaging technology have reported conflicting findings (Gottlob & Welge-Lussen 1987;Leone et al 2008).…”
Section: Introductionmentioning
confidence: 99%